2011
DOI: 10.3892/ijo.2011.1005
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of α1,6-fucosyltransferase in hepatoma enhances expression of Golgi phosphoprotein 2 in a fucosylation-independent manner

Abstract: Golgi phosphoprotein 2 (GP73) is a type II Golgi protein, which was found on examination of the fucosylated proteome as a potential tumor marker for hepatocellular carcinoma (HCC). The serum levels of both total and fucosylated GP73 were increased in the sera of patients with HCC. Fucosylation is one of the most important oligosaccharide modifications involved in cancer and is catalyzed by α1,6-fucosyltransferase (Fut8). In the present study, we investigated the effect of Fut8 overexpression on GP73 production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Kladney et al identified that GP73 expression increased in response to interferon γ and that it was inhibited by tumor necrosis factor α (11). Kawamoto et al demonstrated that α1,6-fucosyltransferase enhanced the expression of GP73 (23). However, the precise mechanism of GP73 elevation in HCC remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Kladney et al identified that GP73 expression increased in response to interferon γ and that it was inhibited by tumor necrosis factor α (11). Kawamoto et al demonstrated that α1,6-fucosyltransferase enhanced the expression of GP73 (23). However, the precise mechanism of GP73 elevation in HCC remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…FUT8 transfers a fucose in the Golgi apparatus and was reported to be localized in the Golgi (19). As described above, FUT8⌬SH3 did not have catalytic activity, which might lead to overall misfolding of FUT8⌬SH3 and its entrapment in the ER.…”
Section: Fut8 Sh3 Domain Influences the Cell-surface Localization Of Fut8mentioning
confidence: 92%
“…FUT8 is considered to be localized in the Golgi, having a typical type II topology (19). However, a previous structural study revealed that the FUT8 luminal domain has a unique C-terminal Src homology 3 (SH3) domain (Fig.…”
mentioning
confidence: 99%
“…The SH3 domain is typical of signal transduction molecules in the cytosol, but is unique to FUT8 compared to other glycosyltransferases (and likely plays are an important role in FUT8’s activity and core fucosylation) [ 44 ]. FUT8 is mainly localized to the Golgi with a type II topology, however, Tomida et al have reported that FUT8 can be partially localized to the cell surface in an SH3-dependent manner [ 44 , 45 ]. Amino acid His535 in the SH3 domain is an essential residue for the enzymatic activity of FUT8, and ribophorin I (RPN1) has been identified as an SH3-dependent binding protein of FUT8, that can stimulate core fucosylation [ 44 ].…”
Section: Alpha-(16)-fucosyltransferase (Fut8)mentioning
confidence: 99%